Adequacy, Ideas and Function of Things and Names on Plato’s Cratylus - Vireira, Celso Oliveira (2012)
The article aims to understand the role of names in Plato’s Cratylus based upon the ontological theory that backgrounds the discussion. From the identi?cation, at some level, of the theory of Ideas follows an attempt to coordinate into an ontological scheme important terms on Plato’s thought as essence and Idea. After establishing the roles of Idea and essence in relation to things comes the effort to prove its correspondence when applied to names. This investigation leads to a new possibility in understanding the relations between names and things based on their functions (when they realize their essence) and on their connection with Ideas. Such an understanding allows one to see the function of names as a simple instrument for reference. If so, there is a plausible justi?cation for the denying of names on the search for knowledge that appears in the aporetic ending of the dialogue.